Gravidez na adolescência no estado do Pará: uma análise epidemiológica e espacial - SANTANA, Michel Martins (2024)
Adolescence corresponds to the period of life between 10 and 19 years old and it is during this period that secondary sexual characteristics, awareness of sexuality, personality structuring, environmental adaptation and social integration occur. In the North region of Brazil, almost 70.0% of women became pregnant before 19 years of age. Inadequate schooling and low family income are related to the early onset of sexual activity, which, in turn, increases the chance of getting pregnant in adolescence. In addition, the high incidence of teenage pregnancy in Brazil and the high prevalence in the state of Pará, make the issue extremely relevant for understanding the socioeconomic relationships that contribute to the perpetuation of teenage pregnancy. The research question of this study is: do municipalities in the state of Para with lower socioeconomic indices have higher rates of live births to mothers between 10 and 19 years old? Objective: To investigate the influence of socioeconomic factors on the occurrence of teenage pregnancy in the municipalities of the state of Pará. Method: This research is observational, descriptive and analytical, as it analyzes the incidence and distribution of live births to adolescent mothers in the municipalities of the state of Pará over a period of 4 years and seeks to identify aggravating factors and/or that predispose to their occurrence, related to the socioeconomic indices of each municipality. The results indicate that we have a worrying scenario with a high incidence of teenage pregnancy in the state of Pará, a situation much more related to the risk behavior of these adolescents than to the HDI in the investigated municipality. It is concluded that there is an urgent need for initiatives to raise awareness for a more responsible lifestyle, despite the disclosure of institutions capable of protecting this teenager in case of probable abuse. Therefore, it is essential to make self-care responsible, through guidelines that can be encouraged in the school and family environment in partnership with municipal health structures.